Plant Diversity Conservation and Tourism Development in the Jalasundra-Mbrumbun Karst Area, Lamongan Regency - Najih, Riyan Riyadlun; Mukhoyyaroh, Naila Izzatul; Kinasih, Umu Intan; Pribadi, Titanio Auditya; Hakim, Luchman (Graduate School, Universitas Brawijaya, 2025)
Karst springs, such as the Jalasundra-Mbrumbun springs in East Java, Indonesia, have considerable potential to integrate natural conservation and tourism development. However, flora inventories and studies examining the relationship between plant diversity and tourism remain limited in karst areas. This study aims to identify plant species in the spring area and to explore tourism-related aspects associated with the site. Plant species were documented through field observations, while plant nomenclature and distribution status were determined using the Royal Botanic Gardens’ Plants of the World Online database. Tourism data were obtained through semi-structured interviews using purposive sampling involving five respondents, as well as direct observation of the four key tourism components (4A). A total of eighteen plant species were identified in the spring area, the majority of which are native species (12 species). Several plant species found in the area are considered sacred, including Ficus kurzii, Ficus benjamina, and Pimelodendron sp. In addition, the presence of an invasive species, Muntingia calabura, poses a significant threat to ecosystem balance. Therefore, preserving native species and controlling invasive species are essential for maintaining spring ecosystem sustainability. Furthermore, attention to the 4A tourism components, alongside native species conservation, represents a key element in strengthening the relationship between conservation and tourism.